PirB regulates asymmetries in hippocampal circuitry - Ukai, Hikari (PLoS One, 2017)
Left–right asymmetry is a fundamental feature of higher-order brain structure; however, the molecular basis of brain asymmetry remains unclear. We recently identified structural and functional asymmetries in mouse hippocampal circuitry that result from the asymmetrical distribution of two distinct populations of pyramidal cell synapses that differ in the density of the NMDA receptor subunit GluRε2 (also known as NR2B, GRIN2B or GluN2B). By examining the synaptic distribution of ε2 subunits, we previously found that β2-microglobulin-deficient mice, which lack cell surface expression of the vast majority of major histocompatibility complex class I (MHCI) proteins, do not exhibit circuit asymmetry. In the present study, we conducted electrophysiological and anatomical analyses on the hippocampal circuitry of mice with a knockout of the paired immunoglobulin-like receptor B (PirB), an MHCI receptor. As in β2-microglobulin-deficient mice, the PirB-deficient hippocampus lacked circuit asymmetries. This finding that MHCI loss-of-function mice and PirB knockout mice have identical phenotypes suggests that MHCI signals that produce hippocampal asymmetries are transduced through PirB. Our results provide evidence for a critical role of the MHCI/PirB signaling system in the generation of asymmetries in hippocampal circuitry.